Sun Tzu the art of war through the ages - Sunzi, active 6th century B.C (Military history from primary sources, 2013)
Illustrated edition with approximately 20 black and white pictures depicting different periods of war. Part of the Military History from Primary Sources series, a new military history range compiled and edited by Emmy Award winning author and historian Bob Carruthers.